Proceedings of the International Business Management Conference, 6th-7th December 2004, Kuantan, Pahang - International Business Management Conference (2004 : Universiti Tenaga Nasional); Norkhairul Hafiz Bajuri @ Mok; Syahrul Ahmar Ahmad; Rohaizat Baharun; Mohd. Noor Azli Ali Khan; Universiti Tenaga Nasional; Tenaga Nasional Berhad (Selangor : Universiti Tenaga Nasional, 2004)
28